Information technologies as a means of overcoming social-cultural barriers in the process of international students training - Subota, Larysa; Kravchuk, Oksana; Davydova, Zhanna; Tverezovska, Nina (Universidad de Carabobo, Venezuela, 2022)
The intensification of the development of digital technologies and their introduction into educational activities has necessitated the use of digital technologies in the educational process of higher educational institutions in order to overcome language barriers in the provision of educational services to foreign students. The purpose of the research lies in identifying the main problematic aspects and prospects for the application of digitalization as a means of overcoming language barriers in the education of foreign students. The methodological base of the academic paper consists of the following methods of scientific research, namely: the method of theoretical analysis and synthesis, analysis and scientific abstraction, comparison and analogy, grouping and cluster analysis based on the kmeans method, generalization and systematization. The results of the conducted research have made it possible to establish that overcoming language barriers in the education of foreign students significantly depends on the level of digitalization of the society and the system of higher education. Intensification of the use of digitalization as a means of overcoming language barriers in teaching foreign students will make it possible to minimize the level of language barriers and ensure the improvement of the quality of the educational process in the online environment through applying digital technologies, as well as create favourable conditions for conducting a simple and understandable language for foreign students.
Las tecnologías de la información como medio de superación de barreras socioculturales en el proceso de formación de estudiantes internacionales
Keywords: higher education seekers; digital technologies; educational activity; language barriers; educational process; digitalization of education